SYSTEMATIC REVIEW : UJI AKTIVITAS ANTI BAKTERI EKSTRAK BUAH ANDALIMAN (ZANTHOXYLUM sp) - Amirah Nahdiah Batubara; Saiful Batubara; Afrilius Simanjuntak (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
One type of spice whose utilization is still very limited is andaliman (Zanthoxylum sp), the Rutaceae tribe which is a typical Batak cooking spice. This study uses a systematic review method. The data used in this study are from research results that have been published in national and international journals. The results of a search for journal publications related to Andaliman Antibacterial Activity (Zanthoxylum sp) for the first phase of the 2012-2022 publication period obtained 34 domestic and foreign journal publications. After conducting a review based on the criteria, 14 journals were selected, 6 Indonesian language journals and 8 English language journals. 24 journals were excluded because they did not meet the criteria. The disc diffusion method is the most widely used method. S aureus and E.coli most dominant of data on Minimum Inhibitory Concentration (MIC) related to the antibacterial effect of andaliman (Zanthoxylum sp).